P-116 Improving provision of timely anticipatory medications at end-of-life for community patients; where have we got to?. (19th November 2022) - Ross, Joy R; Dodds, Nigel
Abstract : Background: An ongoing challenge, both across our healthcare systems and for individual patients and families, remains regarding access to 'just-in-case' (JIC) medications to support symptom control at end-of-life (NICE. Guidance End of life care for adults. Quality standard [QS13]). Our community teams work across 5 CCGs, caring for approximately 1200 patients (own home or care home). Timing, assessment, procurement and administration of such medications, the governance and cost associated with this, particularly out-of-hours, needs further evaluation. Local community processes are not well established, with significant delays. Aim: This work builds on a previous service evaluation of JIC medications provided by the hospice to our community patients (Tran, Lee & Ross, 2021. BMJ Support Palliat Care. 11: A60). Method: Retrospective review of internal prescriptions for medications over 1 month including prescriber, medications given, with more detailed case-note review (of two-thirds) to identify themes/challenges and outcomes. Results: 159 prescriptions were written by doctors (45%) or NMPs over 1 month. 16% of patients required >1 prescription (range 2-7), with peak requests on a Friday. This cohort was elderly, half ≥85 years old; 49% had a primary cancer diagnosis (vs 51% non-malignant), a third also had a dementia diagnosis. Three months later, 85% had died (89% in their usual residence) median time to death 6 days. 20% of prescriptions were a new/urgent referral; 52% required urgent OOH visits. 94% included injectable medications (vs 3 transdermal analgesia; 3 PR paracetamol; 4 other). 73% received injectable opioids (Morphine 57%, Oxycodone 34%, Alfentanil 9%). We saw a 50% reduction in scripts for antiemetics, with reduction in haloperidol (79% to 35%) versus other antiemetics (levomepromazine 47%, cyclizine 14%, metoclopramide 3%) both of which were key outcomes to improve cost-effectiveness from our previous service evaluation. We documented administration of these injectable meds (stats or CSCI) in 55%. Themes/Challenges will also be presented. Conclusion: Projects to evaluate and change practice in this area can be effective; further integrated working to establish and evaluate cost-effective pathways to access medications at end-of-life is essential.